Pharmaceutical Company: Key metrics and Stock performance - Nguyễn, Ngọc Lam ([s.l.], 2020)
Key metrics of pharmaceutical company ; Annual data of key metrics and stock prices from some biggest pharmaceutical companies around the world ; Analysis of correlation between stock price and each key metric of these companies ; Multiple regression model